Serum amino acid responses to three different exercise sessions in male power athletes - Pitkanen, H.; Mero, A.; Oja, S. S.; Komi, P. V.; Pontinen, P. J.; Saransaari, P.; Takala, T. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: The purpose of this study was to investigate serum amino acid responses to 3 different exercise sessions in male power athletes (sprinters and jumpers; n=11). METHODS: All subjects performed 2 running exercise sessions: a short run session (SRS) of 3x4x60 m with recoveries of 120 and 360 sec, and a long run session (LRS) of 20 sec runs with recoveries of 100 sec until exhaustion. Ten subjects performed a strength exercise session (SES) of 90 min. Serum amino acids (n=21) were assayed 10 min before and 10 min after the sessions. Peak blood lactate was analyzed from fingertip blood samples taken 1 and 5 min after the sessions. RESULTS: The before-after comparisons showed that the essential amino acids (EAAs) decreased by 8.7% (p<0.01) and alanine increased by 26.7% (p<0.001) after SRS. Following LRS the EAAs decreased also by 8.7% (p<0.01) and alanine increased by 25.3% (p<0.001). In the sum of all amino acids there were no changes after SRS and LRS but a significant decrease (14.8%; p<0.01) was observed after SES. Also the EAAs decreased (20.6%; p<0.001) but alanine, taurine and citrulline were the only single amino acids with no changes after SES. The peak blood lactate concentrations after SRS, LRS and SES were 13.8+/-1.9, 16.4+/-1.3 and 2.5+/-0.4 mmol/L, respectively. The lactate value after SES differed (p<0.001) from the values observed after SRS and LRS. The comparison of the changes in the serum amino acid concentrations following the 3 exercise sessions revealed that SRS and LRS were very similar but SES differed from SRS and LRS strongly (p<0.01) in the sum of all amino acids. CONCLUSIONS: The current data indicate that the sum concentrations of all amino acids in serum decrease after the strength exercise session but not after the lactic anaerobic running exercises.